Effect of NAA and Chitosan in rooting branches resulting from stem nodes plantation of Kumquat (Citrus japonica) in vitro - Safana, Hazim Sultan; Ibrahim, Majid Abdul-Hameed Ibrahim; Abdul-Kareem Muhammed Abd (Journal of Kerbala for Agricultural Sciences, 2022)
The research was conducted in a Plant Tissue Culture Laboratory, Agricultural Research Department, Ministry of Science and Technology, from December 10/1/2019 to December 30/1/2021, to study the effect of adding auxin NAA at concentrations (1, 2, and 3) mg L-1, and interaction with Chitosan at concentrations (10, 15, 20 and 25) mg L-1, to the culture media MS, to determine the optimal concentration in rooting the branches resulting from the multiplication of micro branches of the Kumquat plants (Citrus japonica), produced from in vivo development of the stem nodes. The results of the study showed that the planting of Kumquat branches in MS media supplemented with 2.0 mg L-1 NAA was a high significant response on rooting percentage (92.0%) and roots number (3.20 plant root-1), added 15 mg L-1 chitosan to the culture media prepared with 2.0 mg L-1 NAA was a significantly increased in same parameters (rooting percentage 80% and roots number 5.60).